Evaluation of Physico-Chemical and Nutritional Properties and Microbial Analysis of Some Local Jam and Jelly in Bangladesh - Mozakkin, Md Jayed Imrul; Saha, Barun Kanti; Ferdous, Taslima; Md Masum, Shah; Quaiyyum, M Abdul (Dhaka University Journal of Applied Science and Engineering, 2023)
In this study, the nutritional and physico-chemical characteristics of ten popular jam and jelly available in local markets of Bangladesh were evaluated. It was found that the moisture contents of the samples were from 21.07-17.83%. The pH range was 2.5-3.4 indicating the acidic nature of jam and jelly samples. The total solid contents of the samples were from 63 to 68% which were very close to BSTI standard value. The total sugar was between 46.10% to 61.0% and the reducing sugar was between 28.27% to 50.3%. It was found that samples contained very less amount of protein, fat and minerals but the carbohydrate content was very high. No heavy metal or microorganism contamination was found but preservatives in some of the samples were found a little higher than standard value. DUJASE Vol. 7(1) 16-21, 2022 (January)